CONVENTIONAL BANK CONVERSION ANALYSIS TO SHARIA BANKS ACOORDING TO THE SERVICES AUTHORITY REGULATION - Nurhadi Nurhadi (Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
OJK (financial services authority) that issues a rule about conventional banks can make changes to business activities into Islamic banks, but not vice versa. Changes must obtain permission and fulfill the requirements. After permission is obtained, it must clearly state the word